Assessment of Anti-Ganglioside Antibodies in Patients Diagnosed With Guillain Barre Syndrome - Hassan, Zahid; Gilani, Atifa; Alamgir, Waseem; Nawaz, Khurram Haq; Ullah, Hikmat; Kazmi, Sakhawat (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the frequency of patients positive for the presence of anti-ganglioside antibodies and factors related to it among the patients diagnosed with Guillian Barre Syndrome (GBS) at our hospital.Study Design: Prospective longitudinal study.Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from Jan to Jun 2019.Methodology: Patients were included in the study once detailed assessment and investigations have been carried out by the consultant neurologist and he has declared the patient suffering from Guillian Barre Syndrome. Anti-ganglioside antibodies were performed on all the patients diagnosed with Guillian Barre Syndrome from the immunology department of the laboratory of our hospital. Factors like age, gender, preceding gastrointestinal infection; sensory involvement and need for mechanical ventilation were related with the presence of Guillian Barre Syndrome in our target population.Results: A total of 30 patients were enrolled in the study. Out of these 22 (73.3%) were positive for the presence of antiganglioside antibodies while 08 (26.4%) did not show the presence of detectable levels of these antibodies in their serum. On fisher exact test preexisting gastrointestinal infection and sensory involvement were statistically significantly related to the presence of anti-ganglioside antibodies among the patients suffering from Guillian Barre Syndrome.Conclusion: Relationship of presence of anti-ganglioside antibodies was strong with the Guillian Barre Syndrome among the patients enrolled in our study. It was even stronger in among the patients who presented with the sensory involvement or those who had a gastrointestinal infection prior to the onset of symptoms of...........